2015
DOI: 10.1103/physrevb.91.245204
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and electronic structure of BiTeI, AuTeI, and PdTeI compounds: A dispersion-corrected density-functional study

Abstract: Semilocal and dispersion-corrected density-functional calculations have been performed to study the crystal structure, equation of state, and electronic structure of metal tellurohalides with chemical formula MeTeI where Me=Bi, Au, or Pd. A comparative investigation of the results of these calculations is conducted, which reveals the role of van der Waals attraction. It is shown that the prediction of crystal structure of metal tellurohalides is systematically improved thanks to the inclusion of van der Waals … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
16
0
3
Order By: Relevance
“…Değiş-tokuş-ilgileşim fonksiyoneli olarak Perdew-Burke-Ernzerhof (PBE) fonksiyoneli [28] kullanılmıştır. Önceki bir yayınımızda [22] van der Waals dispersiyon etkileşmesinin hesaba katılmasının gerekli olduğu açığa çıkmıştır. Bu nedenle, PBE fonksiyoneline ilaveten yarı-ampirik bir dispersiyon potansiyeli [29] kullanılmıştır.…”
Section: Materyal Ve Metotunclassified
See 1 more Smart Citation
“…Değiş-tokuş-ilgileşim fonksiyoneli olarak Perdew-Burke-Ernzerhof (PBE) fonksiyoneli [28] kullanılmıştır. Önceki bir yayınımızda [22] van der Waals dispersiyon etkileşmesinin hesaba katılmasının gerekli olduğu açığa çıkmıştır. Bu nedenle, PBE fonksiyoneline ilaveten yarı-ampirik bir dispersiyon potansiyeli [29] kullanılmıştır.…”
Section: Materyal Ve Metotunclassified
“…BiTeI yarıiletkeninin spin-ayrışmış Rashba bantlarına ait ölçüm [1, [15][16][17] ve hesaplama [18][19][20][21][22][23] sonuçlarını rapor eden çok sayıda yayın çıkmaktadır. Katmanlı bir yapıya sahip olan BiTeI kristalini, ilk-prensip hesaplamaları gerçekleştirerek, incelediğimiz önceki bir yayınımızda [22], BiTeI bant yapısında oluşan Rashba tipi yarılmaların kökeni araştırılmıştır: BiTeI katmanlarının arasındaki bölgelerde içsel bir 2B elektron gazının oluştuğu açığa çıkarılmıştır. Bununla beraber, BiTeI katmanlarının kompozisyonunun birli olması ve bizmut, tellür ve iyot atomlarının elektronegatiflik değerlerinin uygun düşmesi sayesinde, zikredilen içsel 2B elektron gazının maruz kaldığı asimetrik bir içsel elektrik alanın da var olduğu anlaşılmıştır.…”
Section: Introductionunclassified
“…Ref. 8. In this structure, adjacent (unary) layers formed by Bi, Te, and I atoms stack along the c-axis, and the van der Waals (vdW) gap exists in the vacuum region between the Te and I layers.…”
mentioning
confidence: 99%
“…The parameters used for the semiempirical (van der Waals) force field 10 were the same as in Ref. 8. It should be mentioned that although we were inclined to employ a nonempirical van der Waals density functional (in lieu of the semiempirical force field) such as the optB86b-vdW functional, 20 we unfortunately found that the crystal structure of BiTeI was not adequately described by using the optB86b-vdW functional, as discussed in the Appendix.…”
mentioning
confidence: 99%
See 1 more Smart Citation